MODEL PENTAHELIX DALAM TATA KELOLA BAWANG MERAH DI KABUPATEN NGANJUK - Andini Rachmawati; Singgih Manggalou (Journal Publicuho, 2025)
This study aims to analyse the roles of actors within the Pentahelix model: Academia, Business, Community, Government, and Media in the governance of shallot in Nganjuk Regency. The research employs a descriptive qualitative approach through in-depth interviews, observation, and documentation studies. The informants consist of representatives from the Department of Agriculture, the University of Muhammadiyah Malang, UD Pangrukti Tani, the Luru Luhur Farmers’ Group Association, and Radar Nganjuk. The results show that three actors (Government, Academia, and Community) have performed optimally, while two actors (Business and Media) have not yet fully contributed. Academia plays a role through research and farmer training; businesses are involved mainly in seed supply and upstream training; communities act as implementers and technology validators; the government functions as the main coordinator; and the media remains event-driven. The study recommends strengthening the role of businesses in value-added activities, enhancing media engagement through continuous education, and establishing a formal Pentahelix forum to facilitate equal collaboration among actors.